THE CORRELATION BETWEEN ANTENATAL CARE, PARITY AND MATERNAL AGE AMONG PREGNANT WOMEN WITH ANTEPARTUM HEMORRHAGE INCIDENCE AT GONDOSARI COMMUNITY HEALTH CENTER, KUDUS - Erlangga, Akbar Dito; Permatasari, Tissa Octavira; Permana, Ouve Rahadiani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Antepartum hemorrhage is one of the main cause of maternal mortality. The Maternal Mortality Rate (MMR) in Indonesia currently reaches 305 every 100,000 live births which is still quite high from the MDGs target. Risk factors for antepartum hemorrhage will increase with increasing age and maternal parity, while, the cause of maternal death can be prevented via regular Antenatal Care (ANC). This present study aimed to determine the correlation between the frequency of antenatal care, parity, and age of pregnant women with the incidence of antepartum hemorrhage in the Community Health Center, Kudus City.Method: This was an observational analytic study with cross-sectional design. This study used secondary data obtained from maternal cohort books and Local Area Monitoring of Mother and Child Health (PWS-KIA) databooks. Using simple random sampling technique, a total of 323 individuals were recruited. Univariate analysis, bivariate analysis and multivariate analysis were performed on the data obtained.Results: The Spearman?s correlation test showed that there was significant correlation between frequency of Antenatal Care (ANC) (p=0.001), parity (p= 0.001) and age (p=0.001) with antepartum hemorrhage. The correlation coefficient showed that antenatal care (ANC) has a strong negative correlation with antepartum hemorrhage (r= -0.541), parity has a medium correlation with antepartum hemorrhage (r= 0.418) and age has a medium correlation with antepartum hemorrhage (r= 0.465). Multivariate analysis showed that age had the strongest influence on the incidence of antepartum hemorrhage (PR= 274.573), while other variables had the weakest influence smaller effect on the incidence of antepartum hemorrhage (ANC, PR= 0.001 and parity, PR= 0.041)Conclusion: The frequency of antenatal care (ANC), parity and age have correlation with antepartum hemorrhage in the working area in Gondosari Community Health Center, Kudus. Age is the most influential factor in the incidence of antepartum hemorrhage.